Main Movements in Accounting Records’ Development of the Republic of Kazakhstan in the Context of Economic Globalization - BAYDYBEKOVA, Saltanat K.; ABDYKALIEVA, Zhupargul Sh.; TOLEGENOVA, Aida D.; KEREEVA, Aynur R.; BAYTARAKOVA, Botha D. (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
The paper examines the main trends in accounting records’ development of the Republic of Kazakhstan in the context of economic globalization. The article reflects the need of transition to international financial reporting standards, systematization of gathered experience in the context of world economy globalization and theoretical and methodological problems’ development of improving the accounting and auditing systems, identified goals and objectives of the study. The aim of the article is to develop ways to improve the accounting system in the Republic of Kazakhstan in the context of economic globalization and harmonization of accounting records in accordance with International Financial Reporting Standards (IFRS). The article studied the theoretical base of IFRS formation and substantiated the main directions of accounting records’ methodology and organization improvement. There are proposed ways to improve accounting and reporting that meet the modern requirements of IFRS. By means of the proposed procedures’ implementation, there can be carried out a comprehensive and systematic assessment of organization’s efficiency as a whole and the individual departments, identified current priorities of development and predicted their future development in order to develop optimal management decisions.